2013
DOI: 10.1371/journal.pone.0082201
|View full text |Cite
|
Sign up to set email alerts
|

Rhein, a Natural Anthraquinone Derivative, Attenuates the Activation of Pancreatic Stellate Cells and Ameliorates Pancreatic Fibrosis in Mice with Experimental Chronic Pancreatitis

Abstract: Pancreatic fibrosis, a prominent histopathological feature of chronic pancreatitis (CP) and pancreatic ductal adenocarcinoma, is essentially a dynamic process that leads to irreversible scarring of parenchymal tissues of the pancreas. Though the exact mechanisms of its initiation and development are poorly understood, recent studies suggested that the activation of pancreatic stellate cells (PSCs) plays a critical role in eliciting such active course of fibrogenesis. Anthraquinone compounds possess anti-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 54 publications
(62 reference statements)
2
41
0
Order By: Relevance
“…Sonic hedgehog plays critical roles in inflammation, fibrogenesis and tumorigenesis in addition to embryonic developmental processes. Previous work of our research group manifested that the SHH signalling pathway played an important role in sustaining fibrotic processes in cerulein‐induced chronic pancreatitis (Tsang et al , ). In the present study, we demonstrated that SHH/GLI1 signalling was a transcriptional target of NF‐κB during TGF‐β‐dependent fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Sonic hedgehog plays critical roles in inflammation, fibrogenesis and tumorigenesis in addition to embryonic developmental processes. Previous work of our research group manifested that the SHH signalling pathway played an important role in sustaining fibrotic processes in cerulein‐induced chronic pancreatitis (Tsang et al , ). In the present study, we demonstrated that SHH/GLI1 signalling was a transcriptional target of NF‐κB during TGF‐β‐dependent fibrogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this idea, during development, the expression pattern of type XVIII collagen in the ureter bud is responsive to changes in SHH expression in the epithelium [29]. In the adult, hedgehog (Hh) signaling can regulate lung fibrosis [30], and expression of SHH and GLI were correlated with cerulean-induced fibrosis in the pancreas [31], suggesting that SHH may be a regulator of collagen. In this study we will examine if collagen production is responsive to SHH signaling in the penis and in the CN, and to CN regulation, and thus may provide a novel avenue for clinical intervention post prostatectomy and in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works of our group showed that aberrant activation of NF-κB was observed in fibrotic and inflammatory conditions of the pancreas [17]. Sonic hedgehog (SHH) and its immediate effector glioma-associated oncogene (GLI1), which are the target genes of NF-κB, were accordingly elicited in response to tissue injury and exogenous stimulation of proinflammatory mediators including TGF-β and TNF-α [17,18]. However, the molecular details of the tight control of NF-κB activation and up-regulation of SHH in fibrogenesis have yet clearly elucidated.…”
Section: Introductionmentioning
confidence: 82%
“…A number of reports demonstrated that TGF-β is a potent inducer for the activation of NF-κB signaling [15,16]. Previous works of our group showed that aberrant activation of NF-κB was observed in fibrotic and inflammatory conditions of the pancreas [17]. Sonic hedgehog (SHH) and its immediate effector glioma-associated oncogene (GLI1), which are the target genes of NF-κB, were accordingly elicited in response to tissue injury and exogenous stimulation of proinflammatory mediators including TGF-β and TNF-α [17,18].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation